Why do political coalitions collapse in Lesotho?: a case study of coalition politics in Lesotho from 2012 – 2017 - Mohlamenyane, Lerato (My University, 2018)
The road to a politically stable Lesotho has not been an easy one following the country gaining its independence on October 4th 1966. The post-independence period saw the country transition towards a period of authoritarian civilian rule, to a military dictatorship and finally an era of one-party dominance democracy. Moving towards this era has proved to be a great challenge as for many years Lesotho’s institutions, as well as the electoral model, were viewed as not fully aligned with the values and principles of a democracy such as the representation of the different political parties in Parliament. In an attempt to remedy this problem, a more representative electoral model in the form of the Mixed Member Proportional (MMP) system was introduced. To date, Lesotho has had three elections in the space of five years. These elections have produced three coalition governments, two of which have collapsed following internal disputes and divisions amongst the coalition partners and one which is currently in power. This research report seeks to examine what has been the causal source/s of the coalition collapses which have taken place. Findings from this case-study highlight that the lack of thresholds within the electoral model and floor-crossing provisions have contributed to a volatile Parliament which comprises of small political parties that have the power to make or break these coalitions by either joining them to constitute a majority government or by destabilising the coalitions when crossing the floor in Parliament. Another key finding presents that the political culture of Lesotho which consists of a self-serving elite has significantly contributed to an extremely polarised environment which has affected the public sector as well as the military, thus threatening the democracy of the of the country. These challenges that the country faces require Lesotho to undergo a process of reforms. These reforms which have been instituted by the Southern African Development Community (SADC) and address the three key areas which have been of great challenge to Lesotho and these include the security sector, the electoral model, and the Constitution. As SADC focuses on these areas of concern, we can only hope that the reforms will be implemented with the strong political will from the leaders of the country.
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts in Political Studies to the Faculty of Humanities, School of Social Sciences, University of Witwatersrand, 2018
Keywords: Lesotho--Politics and government; Lesotho--Social conditions